2004
DOI: 10.5194/angeo-22-2325-2004
|View full text |Cite
|
Sign up to set email alerts
|

Bow shock specularly reflected ions in the presence of low-frequency electromagnetic waves: a case study

Abstract: Abstract. An energetic ion (E≤40 keV) event observed by the CLUSTER/CIS experiment upstream of the Earth's bow shock is studied in detail. The ion event is observed in association with quasi-monochromatic ULF MHD-like waves, which we show modulate the ion fluxes. According to three statistical bow shock position models, the Cluster spacecrafts are located at ∼0.5 R E from the shock and the averaged bow shock θ Bn0 is about ∼30 • . The analysis of the threedimensional angular distribution indicates that ions pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 33 publications
4
50
2
Order By: Relevance
“…7-9. Both populations are gyrophase bunched and similar to those observed in the shock foot region (Meziane et al, 2004a). Paschmann et al (1981) and Sckopke et al (1983) showed that the ion distribution in the upstream foot region of a quasi-perpendicular bow shock is consistent with a partial ring distribution that originates from the reflected solar wind at the bow shock.…”
Section: Foot Regionmentioning
confidence: 52%
See 4 more Smart Citations
“…7-9. Both populations are gyrophase bunched and similar to those observed in the shock foot region (Meziane et al, 2004a). Paschmann et al (1981) and Sckopke et al (1983) showed that the ion distribution in the upstream foot region of a quasi-perpendicular bow shock is consistent with a partial ring distribution that originates from the reflected solar wind at the bow shock.…”
Section: Foot Regionmentioning
confidence: 52%
“…The flow directions of both populations point away from the subsolar region. The field-aligned tailward flow with substantial gyromotion of both populations is similar to the reflected-gyrating component in the terrestrial bow shock foot region (Paschmann et al, 1981;Sckopke et al, 1990;Meziane, 2004a). It is worth reminding ourselves that the elevation-azimuth pattern of the gyrating ions as shown in Fig.…”
Section: Two-layer Structurementioning
confidence: 98%
See 3 more Smart Citations